ISARC 2008 - Proceedings From the 25th International Symposium on Automation and Robotics in Construction 2008
DOI: 10.22260/isarc2008/0084
|View full text |Cite
|
Sign up to set email alerts
|

Using the MD CAD Model to Develop the Time-Cost Integrated Schedule for Construction Projects

Abstract: This paper presents a work-item-based scheduling system that employs MD CAD model, Object Sequencing Matrix (OSM), and Genetic Algorithms (GAs) to generate the time-cost integrated schedule for construction projects. Consisting of MD CAD objects, the MD CAD model ensures the consistency and efficiency of information processing and integration in project planning. In the development of MD CAD model-based scheduling system, the Object Sequencing Matrix (OSM) is adopted to formulate a construction sequence of bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Furthermore, BIM software is very complex which creates difficulties in terms of manipulation. For instance, a large amount of information is required from early stage of BIM design (Ding et al, 2012;Feng et al, 2010). Some studies also reported the concerns of industry practitioners that BIM software is too 736 ECAM 22,6 precise which may hinder designer's creativity (Berwald, 2008;Morton, 2012).…”
Section: Technical Defects Of Bimmentioning
confidence: 99%
“…Furthermore, BIM software is very complex which creates difficulties in terms of manipulation. For instance, a large amount of information is required from early stage of BIM design (Ding et al, 2012;Feng et al, 2010). Some studies also reported the concerns of industry practitioners that BIM software is too 736 ECAM 22,6 precise which may hinder designer's creativity (Berwald, 2008;Morton, 2012).…”
Section: Technical Defects Of Bimmentioning
confidence: 99%
“…Feng et al [22] studied the application of a time-cost integrated schedule for construction project within BIM constraints, to which they refer as a visualized time-control model. The addition of a cost component in such a model enables a fifth dimension (5D).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondary data collection in the form of soil test data, SNI regulations, shop drawing, material and equipment prices in 2019, labor prices in 2019, and AHSP in 2019. While primary data collection is in the form of time schedule, costs, and technical specifications (Xue et al, 2022;Feng et al, 2010). Analysis of structural modelling using SAP 2000 Version 14 application program with live load in accordance with each type of building in the soft and hard soil classification of the earthquake area 5.…”
Section: Methodsmentioning
confidence: 99%